TEKNIK PERIWAYATAN HADIS - Muhammad Fitrah Waila Zamzani; Muhammad Ali (AL-BAYAN INSTITUTE, 2025)
Hadith is the second primary source of Islamic law after the Qur'an, making its authenticity and accuracy essential. This paper examines the transmission techniques used by classical scholars to ensure the originality and credibility of the Prophet Muhammad’s teachings. It explores the definition of hadith transmission, qualifications of transmitters—including justice (‘adālah), precision (ḍabṭ), and connected chains (ittisāl al-sanad)—and the two main methods of narration: verbatim (lafẓan) and by meaning (ma’nan). It also details eight methods of receiving and delivering hadith (al-taḥammul wa al-adā’), such as listening, reading, authorization (ijāzah), handover (munāwalah), written communication (mukātabah), notification (‘ilām), bequeathing (waṣiyyah), and discovery (wijādah). This study is vital in preserving the authenticity of Islamic teachings and preventing distortions